2020
DOI: 10.1111/exd.14202
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphisms are associated with psoriasis susceptibility and the clinical response to calcipotriol in psoriatic patients

Abstract: Psoriasis is a common genetic disease characterized by hyperproliferation and disordered maturation of keratinocytes. To date, many association studies between psoriasis and VDR gene have been conducted, but the results are controversial. Furthermore, vitamin D 3 analogue has anti-psoriatic activity; however, the clinical response is variable. This study was conducted to explore whether VDR gene polymorphisms are associated with psoriasis susceptibility and clinical response to calcipotriol in psoriatic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…26,45 The therapeutic action of the active forms of vitamin D is mediated by its receptor, VDR. Additionally, the VDR polymorphism is linked to psoriasis susceptibility 27,28 and susceptibility of psoriatic patients to the vitamin D-based treatment. The reduced VDR levels in psoriatic skin are related to the reduced tight junctions.…”
Section: Con Clus I On S and Per S Pec Tive Smentioning
confidence: 99%
“…26,45 The therapeutic action of the active forms of vitamin D is mediated by its receptor, VDR. Additionally, the VDR polymorphism is linked to psoriasis susceptibility 27,28 and susceptibility of psoriatic patients to the vitamin D-based treatment. The reduced VDR levels in psoriatic skin are related to the reduced tight junctions.…”
Section: Con Clus I On S and Per S Pec Tive Smentioning
confidence: 99%
“…Vitamin D3 analogues have long been used as anti‐psoriatic agents, but the elicited clinical response is quite variable. Genotyping analysis for VDR gene polymorphisms found that VDR gene polymorphisms are closely associated with PSO susceptibility and clinical response to calcipotriol in PSO patients 84 . This study suggests that VDR gene sequencing may be performed to predict PSO treatment response to calcipotriol.…”
Section: Pharmacology and Drug Deliverymentioning
confidence: 75%
“…Interestingly, several studies identified an association between polymorphisms of vitamin D receptor (VDR) and psoriasis susceptibility [ 43 ]. However, this is still controversial [ 53 , 54 ]. The mechanism of vitamin D is mediated by the vitamin D receptor (VDR), and after its activation, it interacts with retinoid X receptor (RXR) to form a heterodimeric complex.…”
Section: Current Marketed Therapiesmentioning
confidence: 99%